Exploring the Effectiveness of E-Learning in Fostering Innovation and Creative Entrepreneurship in Higher Education - Marviola Grace Hardini; Tarisya Khaizure; Gelard Godwin (Pandawan Sejahtera Indonesia, 2024)
This research aims to explore the effectiveness of implementing E-Learning in increasing innovation and creativepreneur skills of students in higher education. By focusing on the digital learning environment, this research wants to identify the impact of using E-Learning platforms on the development of students' creative and entrepreneurial ideas. The research method involves collecting quantitative data through online surveys and qualitative through in-depth interviews with students and lecturers. The data is then analyzed to measure the level of effectiveness of E-Learning in providing support for innovation and creativepreneurship skills. It is hoped that the results of this research will provide new insight into the potential of E-Learning in increasing students' creativity and entrepreneurial spirit in the digital era. It is hoped that the conclusions of this research can provide a basis for developing more effective online learning strategies in supporting innovation and entrepreneurship in higher education.